PENGEMBANGAN AUGMENTED REALITY TITRATION (ART) UNTUK MELATIH KETERAMPILAN PSIKOMOTORIK PESERTA DIDIK PADA KONSEP TITRASI ASAM KUAT-BASA KUAT - Dede Miftahul Anwar, -; Muhammad Nurul Hana, -; Ijang Rohman, - (2019)
The background of this research is the importance of virtual experiments to obtain data and train the skills of students in titration experiments. The purpose of this study is to produce a product in the form of an Augmented Reality Titration (ART) application to practice the skill of adjusting the homogeneity of the solution and determining the end point of the titration. The research method used is Developmental research and ADDIE (Analysis, Design, Development, Implementation, Evaluation) was included in the product development step, then at the end of the research conclusions and final product revisions are made. Based on the results of the study, the following conclusions were obtained: 1) Psychomotor skills in strong base acid titration included the selection and design of the titration device, cleaning the burette, preparation of the analyte solution, standardization, Erlenmeyer shake technique, and rotating technique tap. 2) Elements in ART consist of the preparation stage and the implementation stage in the titration process of strong base acids displayed in the form of simulations. 3) Based on the results of the students' responses, it is known that almost all students gave good responses to the ART application based on aspects of the menu display, the preparation stage, the process stage, and navigation. 4) Based on the results of the teacher's response that aspects of work procedures and navigation are known, the teacher provides a good response to the application of ART.